Analysis of the Alignment of Indonesian Language Textbook Content with the Content Standards of the Independent Learning Curriculum - Aicha Lagrima wijaya; Hary Soedarto Harjono; Rustam Rustam (STAI Miftahul Ula Nganjuk, 2024)
This study aims to determine the alignment of the Indonesian language textbook content for Grade X (Phase E), used by SMK Baiturrahim Jambi students, with the learning outcomes (LO) specified in the Content Standards by the Assessment and Curriculum Standards Agency, Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia, within the